'"Shall we gather at the river?": the folklore and trauma of Toni Morrison's landscape in Sula'. (2nd January 2021) - Gooch, Catherine D.
ABSTRACT: In 'The Site of Memory, ' Toni Morrison suggests that 'the act of imagination is bound up with memory' (98). She goes on to compare the Mississippi River to writers, 'remembering where we were, what valley we ran through, what the banks were like' (99). As I demonstrate in this article, it would be a mistake to think of this comparison as a mere metaphor. In this essay, I examine how the characters in Sula rely on and struggle with their communal memories and trauma as they are tied to the river that runs through the Bottom. I argue that Morrison uses the river as a focal point to express the intersection of memory, history, and trauma, both for the individual characters in the book and the Black community at large. Furthermore, I argue that Morrison responds to this violent past by integrating popular folktales and signifying on them in order to help us, and the characters, understand the perils of both the social and natural landscape. Ultimately, I conclude that the presence of the rivers and popular folktales are sites of memory that invoke the histories of oppression that have shaped the lives of the characters in Sula.